Teknologi Pengolahan Hasil Perikanan Menjadi Produk Makanan Jajanan di Desa Sungai Geringging, Kecamatan Kampar Kiri, Kabupaten Kampar, Riau - Sukendi Sukendi; Thamrin Thamrin; Ridwan Manda Putra; Eddiwan Eddiwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Sungai Geringging Village is one of the fishing-producing villages in Kampar district. So far, fishery products have not been used for processing into snack products. Processing fishery products into snack products can increase the economic value of fishery products. The purpose of this community service activity is to provide science and technology to members of the Sinar Mentari Business Group, Sungai Geringging Village, Kampar Kiri subdistrict, Kampar Regency in processing fishery products into snack food products in the form of fish skin chips, fish surimi, fish sausage, and fish dimsum as well as technology for using good packaging and packing. The method used is the lecture method, discussion, and direct practice in the field about the material that has been discussed. The results of the evaluation of changes in knowledge of 10 members of the Sinar Mentari Business Group showed that 8 people (80.00%) had been able to absorb the material given with a very good predicate (A value), 2 people (20.00%) could absorb the material given. with a good predicate (B value), while those with sufficient predicate (C value) and less predicate (D value) were not found. The results of the skills evaluation carried out showed that members of the Sinar Mentari Business group had tried to process fishery products into snack food products in the form of fish skin chips, fish surimi, fish sausage, and fish dimsum as well as good packaging and packing technology. While the results of the impact evaluation carried out showed that members of the Sinar Mentari Business group who were housewives from members of the Karya Mandiri Cultivation Group had a side activity, namely processing the results of fish cultivation carried out by their husbands into snack food products in the form of fish skin chips, fish surimi, fish sausage, and fish dimsum as well as good packaging and packing technology.